Peculiarities of asthenic syndrome in patients with diabetes mellitus type 2 in the clinical and medical-psychological context - V. V. Chugunov; O. V. Tkachenko; N. V. Danilevska (Zaporozhye State Medical University, 2017)
Aim - to determine the peculiarities of asthenic syndrome in patients with diabetes mellitus (DM) type 2 in the clinical and medico-psychological context. Materials and methods. 543 patients with DM type 2 were examined. The first clinical group (CG-1) consisted of 57 patients with DM type 2 of mild severity; the average age in the group was (51.80 ± 1.28) years. The second clinical group (CG-2) was made up of 312 patients with DM type 2, moderate severity; the average age in the group was (55.10 ± 1.12) years. The third clinical group (CG-3) included 174 patients with DM type 2, severe degree of severity; the average age in the group was (the 61.80 ± 0.85) years. Research methods: clinical-anamnestic, clinical-psychopathological, statistical. Results. Asthenic syndrome was detected in 52.30 % of patients with DM type 2 and by the frequency of prevalence it ranked third - after dyssomnia and psychoorganic syndromes. A direct correlation of asthenic syndrome and the severity of DM type 2 (г = 0.68, p < 0.05) was established. Risk factors for the occurrence of asthenic syndrome in patients with DM type 2 were moderate and severe degrees of DM type 2, obesity, discirculatory encephalopathy, heart failure. In CG-1 and CG-2 the dominance of such a component of fatigue as "mental fatigue" was revealed, whereas the "physical fatigue" component has reached dominant values only in CG-3. Conclusions. The peculiarities of asthenic syndrome in patients with DM type 2, and the frequency of its occurrence among the investigated population were studied. Correlation of asthenic syndrome with severity of DM type 2 and concomitant somatic pathology were established. Organic etiology of asthenic syndrome in patients with DM type 2was proved. Understanding of the stages of asthenic syndrome development in patients with type 2nd DM was extended.